2022
DOI: 10.1007/s00421-022-04974-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat acclimation does not attenuate hepcidin elevation after a single session of endurance exercise under hot condition

Abstract: Purpose We sought to determine the effects of heat acclimation on endurance exercise-induced hepcidin elevation under hot conditions. Methods Fifteen healthy men were divided into two groups: endurance training under hot conditions (HOT, 35 °C, n = 8) and endurance training under cool conditions (CON, 18 °C, n = 7). All subjects completed 10 days of endurance training (8 sessions in total), consisting of 60 min of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The present study is placed as a follow-up determination of previous research which reported the effect of HA on the hepcidin response following endurance exercise in a hot environment [ 23 ]. Thus, the subjects and experimental design were thus identical to that study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study is placed as a follow-up determination of previous research which reported the effect of HA on the hepcidin response following endurance exercise in a hot environment [ 23 ]. Thus, the subjects and experimental design were thus identical to that study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present study is placed as a follow-up determination of previous research which reported the effect of HA on the hepcidin response following endurance exercise in a hot environment [ 23 ]. Thus, the subjects and experimental design were thus identical to that study [ 23 ]. For determination of sample size, we referred to previous studies that demonstrated large effects of thermoregulatory adaptations (e.g., lower core temperature during endurance exercise in a hot environment) after HA [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations